2020
DOI: 10.1159/000509669
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of High-Risk HPV Genotypes with Pap Test Findings: A Retrospective Study in Eastern Province, Saudi Arabia

Abstract: Introduction: High-risk human papillomavirus (HR HPV) is found to be responsible for 4.5% of cancer in general, primarily cervical cancer. We aim here to highlight the prevalence and genotypes of HR HPV and correlate its association with Pap tests’ results, which are still not well known in the Eastern Province of Saudi Arabia. Methods: Over 7 years (2013–2019), the results of 164 Saudi women coinvestigated for HR HPV along with Pap tests were collected from the archive of King Fahd University Hospital. Only w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In our study, similar to the study by Kussaibi H. et al [20], a high correlation was found between HPV-DNA test and positive cytology and biopsy. There was a significant correlation between HPV-DNA test and cervicovaginal smear result and cervical biopsy (p = 0.0003, p = 0.0002, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, similar to the study by Kussaibi H. et al [20], a high correlation was found between HPV-DNA test and positive cytology and biopsy. There was a significant correlation between HPV-DNA test and cervicovaginal smear result and cervical biopsy (p = 0.0003, p = 0.0002, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, risk stratification strategies that can better identify underlying or incipient CIN2, CIN3, adenocarcinoma in situ (AIS), or cancer (CIN2+) with less resource waste are needed in HPV-positive patients with LSIL. However, most of the related articles published to date have mainly investigated HPV-positive patients with LSIL using the cytology as a primary screening method but not the HPV testing [17][18][19][20][21]. Moreover, no study has yet addressed application of the 2019 ASCCP guidelines in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Across the world, 95% of cervical cancer are caused by high‐risk human papillomavirus (HR‐HPV) infection 1 . Dozen of HR‐HPV types are highly involved in cervical cancer, and the prevalence and genotypes of HR‐HPV are associated with several factors, such as different locations and ethnicities 2,3 . Persistent HR‐HPV infection can lead to an increased incidence of cervical and intraepithelial neoplasia, and effective inoculation of the HPV vaccine can effectively reduce the risk of invasive cervical cancer 4–6 .…”
Section: Introductionmentioning
confidence: 99%